Using Computerized Provider Order Entry to Enforce Documentation of Tests with Pending Results at Hospital Discharge - Cadwallader, J.; Asirwa, C.; Li, X.; Kesterson, J.; Tierney, W.M.; Were, M.C. (Applied Clinical Informatics, 2012)
Background: Small numbers of tests with pending results are documented in hospital discharge summaries leading to breakdown in communication and medical errors due to inadequate followup.Objective: Evaluate effect of using a computerized provider order entry (CPOE) system to enforce documentation of tests with pending results into hospital discharge summaries.Methods: We assessed the percent of all tests with pending results and those with actionable results that were documented before (n = 182 discharges) and after (n = 203 discharges) implementing the CPOE-enforcement tool. We also surveyed providers (n = 52) about the enforcement functionality.Results: Documentation of all tests with pending results improved from 12% (87/701 tests) before to 22% (178/812 tests) (p = 0.02) after implementation. Documentation of tests with eventual actionable results increased from 0% (0/24) to 50% (14/28)(p<0.001). Survey respondents felt the intervention improved quality of summaries, provider communication, and was not time-consuming. Conclusions: A CPOE tool enforcing documentation of tests with pending results into discharge summaries significantly increased documentation rates, especially of actionable tests. However, gaps in documentation still exist.
Keywords: Patient Discharge; Routine Diagnostic Tests; Medical Order Entry Systems; Documentation; Medical Errors